Nomenclatural notes and lectotypification for Phyllanthus racemiger (Phyllanthaceae) in Brazil - Mendes, Jone Clebson Ribeiro; Torres, Alicia Marques; Orlandini, Priscila; de Sales, Margareth Ferreira (Phytotaxa, 2020)
As the taxonomic report of Phyllanthus is about to be published for Flora of Brazil online 2020, we wish to formalize lectotypification for one species of Phyllanthus and make amendment to the epithet.